Optimalisasi Media Digital sebagai Sarana Penguatan Karakter Siswa Sekolah Dasar di Abad 21 - Lase, Indah Wijaya; Zai, Eka Periaman (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Digital technology in the 21st century plays a crucial role in elementary education, not only as a medium for delivering information but also as a tool for strengthening students' character, including cooperation, responsibility, and self-confidence. This qualitative descriptive research was conducted on August 7, 2025, with fourth-grade students at UPTD SDN 070986 Ononamolo1 Lot in Pancasila Education subject. Data were collected through interviews, observations, and implementation of interactive media, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that the purposeful use of interactive PowerPoint presentations can enhance student engagement and strengthen character values in a more engaging and meaningful way.